Spinning Process Test and Optical Topography Measurement Technology for the Shell with Longitudinal and Latitudinal Inner Ribs. (18th December 2019) - Liang, Wei; Lv, Qiongying; Guan, Lin; Xing, Zhigang
Abstract : The paper studies the complicated problem in the spinning process of the shell with longitudinal and latitudinal inner ribs. The finite element software ABAQUS is used to establish the finite element model of the cylindrical shell with the longitudinal and latitudinal inner ribs. The numerical simulation of the spinning process is carried out. The stress distribution and strain distribution of the inner and outer surfaces during the spin-forming process are determined, and the orthogonal test method is used to determine the optimization process test parameters. The influence of the main process parameters on the wall thickness difference of the inner rib shell is obtained by the range analysis: wall thickness reduction rate > rotary wheel feed speed > rotor working angle (arranging according to their influences). And then the corresponding process parameters recommended by the spinning test are given. The measurement problem of inner ribs is solved by building of the robot shape measurement system which helps detect the three-dimensional shape of the inner ribs, and the precision of the spun sample was detected by the point cloud deviation comparison.